Diagnosis in childhood: Compared interventions in different contexts - Naruli, Maurizio; Nitoglia, Daniele; Paoletti, Matteo; Polli, Melania; Valentini, Simone (Quaderni di Psicologia Clinica, 2024)
In Italy, diagnoses during developmental age are increasing; some literature considers this phenomenon a step forward towards inclusion, while others raise doubts about its usefulness. Through six intervention cases, the article aims to study the affective symbolisations which accompany the diagnosis in developmental age across different contexts. This has important implications for clinical psychological intervention, as the psychologist can gather information about the intervention context from the diagnosis, the way it was produced, and how it is handled. In the first two experiences, professionals work in the school setting with diagnosed children and adolescents, encountering intense power conflicts between the school and families around the diagnosis. In the following two cases, the focus is on the teachers’ perspective, grappling with the issue of managing variability within class groups, which the diagnosis does not resolve. In the final two experiences, professionals work within services external to the school, starting from a collusive failure between the school and families of children with adaptation problems to school life.